Patologia comparada de infecção nasal causada por Conidiobolus lamprauges e Pythium insidiosum em ovinos - Ubiali, Daniel Guimarães (2012)
Thirty cases of fungal or fungal-like rhinitis in sheep caused by Conidiobolus lamprauges (n=15) or Pythium insidiosum (n=15) were morphologically investigated. The diagnoses were based on the histopathological lesions but were confirmed by immunohistochemical identification of the aetiological agent. Lesions from cases of conidiobolomycosis were characterised by granulomatous rhinitis with numerous multinucleated giant cells, macrophages and a limited number of eosinophils and neutrophils that were surrounded by amorphous Splendore-Hoeppli reactions and hyphae. Conversely, pythiosis histological lesions consisted of severely necrotising eosinophilic rhinitis with negatively stained structures representing fungal hyphae that were surrounded by granular and eosinophilic Splendore-Hoeppli material. Both ethiologic agents were positive in GMS and negative in PAS stain. The majority of these differences between the types of fungal or fungal-like infection were associated with the macroscopic aspects of the lesion, the inflammatory cell population, the fungal morphology and the localisation of hyphae by immunohistochemistry.